A Comparison of Immigrant Languages and Varieties in the Linguistic Landscape of Two Towns in Spain: Madrid vs. Málaga - Esteba-Ramos, Diana; Sáez Rivera, Daniel M. (My University, 2014)
Inmigration and its linguistic consequences in a country are not always of the same nature everywhere in the whole territory of the nation. One of the tokens can be the population arrived from the 90s until recently in Madrid, mainly Latin-American, who bring their own varieties of Spanish -and also Native-American languages-, but also Chinese and Arabs, bringing exotic kinds of writing to the Linguistic Landscape of Madrid, and many others, amounting till 60 languages (Broeder/Mijares 2003: 64), 30 of them viewed in the Linguistic Landscape of Madrid (Castillo Lluch/Sáez Rivera 2011). In the Andalucian context, Málaga is known as the main focus of migration movements: more than the 30% of the foreigners coming to live in Andalucia settles down in Málaga, even more than in the capital of the region, Sevilla. In the city center, around the 12% of the inhabitants are immigrants, specially non europeans. In a previous study of the Linguistic Landscape of the city center (Esteba Ramos 2013), it is shown that this population had a limited appearance in public texts, and so its languages. Therefore, theoretically framed in the sociolinguistic field of Migrant Linguistics and the Linguistic Lanscapes studies, we try to compare how immigrant languages and varieties are displayed in the Linguistic Landscapes of Madrid and Málaga using as a comparison other works and previous research performed by the own researchers and new fieldwork for this study. One of the critical points of the comparison consists of checking whether the urban-geographical patterns of Linguistic Landscape found in Madrid (Sáez Rivera/Castillo Lluch 2011) and Sevilla (Pons 2012) are also found in Málaga and until what extension, and how the textualization of signs differs and the patterns of lexicalization displayed in them. Bibliography Broeder, Peter/Mijares, Laura (2003): Plurilingüismo en Madrid. Las lenguas de los alumnos de origen inmigrante en Primaria. Madrid: CIDE / Comunidad de Madrid. <http://lyrawww.uvt.nl/~broeder/pub02a10.htm> Castillo Lluch, Mónica/Sáez Rivera, Daniel M. (2011): “Introducción al paisaje lingüístico de Madrid”, Lengua y Migración 3, pp. 73-88. Esteba Ramos, Diana (2013): “Aproximación al paisaje lingüístico de Málaga”, Recherches 7 (forthcoming) Pons Rodríguez, Lola (2012): El paisaje lingüístico de Sevilla: Lenguas y variedades en el escenario urbano hispalense. Sevilla: Diputación de Sevilla.
Keywords: Multilingüismo; Paisaje lingüístico